IMPLEMENTATION OF MARKETING MIX AND CUSTOMER SATISFACTION AT BERYL'S CHOCOLATE KINGDOM MALAYSIA STORE (Case Study on Students Participating in KKL Management and Accounting Study Program of STIE Sutaatmadja Subang 2019) - Sonia Karmila; Bismantara Bismantara (STIESA Press, 2020)
This research aims to give an overview of the implementation of four elements of marketing mix (product, price, place, promotion) and consumers satisfaction in Beryl’s Chocolate Kingdom Store. Data were collected from 104 consumers by involving STIE Sutaatmadja students as a sample that representing consumer satisfaction. The population used in this research are students of STIE Sutaatmadja as the consumers of Beryl’s Chocolate Kingdom. The technique of sample selection used random sampling with slovin method (? = 5%). Survey method that used are observation, interview and a structured questionnaire. These results indicate Beryl’s Chocolate Kingdom Store has a quite good marketing mix. And, the questionnaire result showed 80,41% consumers are satisfied with Beryl’s Chocolate Kingdom.